Biologic Formulations but Not an Interrow Living Rye Ground Cover Reduced Incidence of Tomato Spotted Wilt Virus in Tomato. Issue 4 (3rd July 2016) - Murphy, John F.; Morawo, Tolulope; Monday, Tyler; Lau, Jeekin; Foshee, Wheeler; Fadamiro, Henry
ABSTRACT: Tomato spotted wilt virus (TSWV) is a persistent threat to tomato ( Solanum lycopersicum L) production, with diseased plants exhibiting reduced growth and direct effects on tomato fruit. TSWV incidence and associated yield losses in tomato plants were assessed with two interrow soil treatments (rye ground cover and bare ground) and four levels of biologic treatments, Make, Agricen, Make + Agricen, and a water control. Tomato plants treated with the biologic formulations in the rye interrow treatment had lower TSWV incidence than the water control, although this did not translate to improved fruit yield. No difference in fruit yield occurred between rye and bare soil interrow treatments. Because biologic treatments reduced TSWV incidence, consideration should be given to integrating them with production practices.